Facing death, returning to life: A qualitative analysis of MDMA-assisted therapy for anxiety associated with life-threatening illness - Barone, William; Mitsunaga-Whitten, Michiko; Blaustein, Lia Osunfunláyò; Perl, Phillip; Swank, Marisa; Swift, Thomas Cody (Frontiers in Psychiatry, 2022)
Anxiety associated with life-threatening illness (LTI) is a pervasive mental health issue with a wide impact. A spectrum of traditional pharmacotherapies and psychotherapies are available, but offer varying success in reducing symptoms and improving quality of life. We explore a novel therapy for this condition by assessing prominent thematic elements from participant narrative accounts of a phase 2 clinical trial of Methylenedioxymethamphetamine-Assisted Therapy (MDMA-AT) for treating anxiety associated with LTI. Semi-structured qualitative interviews were conducted with adult participants three months following completion of a phase 2 clinical trial for clinically elevated anxiety associated with LTI. This qualitative analysis sought to complement, clarify, and expand upon the quantitative findings obtained from the clinical trial and to further understand the process and outcomes of the treatment. Available interviews from 6 of 18 participants were coded and analyzed using an interpretative phenomenological analysis (IPA) methodological framework. All participants reported lasting personal benefits and enhanced quality of life that extend beyond quantifiable symptom reduction. Specifically, participants spoke about important elements of the therapeutic process including existential or mystical-type experiences, the ability to process traumas both associated with and unrelated to the illness, acceptance of life and death, safety and connection in the treatment, and emotional uncoupling from their illness. Participants reported the treatment led to increased self-awareness, improved relationships, and an increased ability to cope with illness-related anxiety. Participant narratives also showed a reconnection to life and greater emotional resilience in response to trauma and medical relapse. Limitations and challenges encountered in conducting this study are discussed along with implications for theory and clinical treatment.